2011
DOI: 10.1074/jbc.m111.238410
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Neutralization of the Major Toxic Component from the Scorpion Centruroides noxius Hoffmann by a Human-derived Single-chain Antibody Fragment

Abstract: It has previously been reported that several single-chain antibody fragments of human origin (scFv) neutralize the effects of two different scorpion venoms through interactions with the primary toxins of Centruroides noxius Hoffmann (Cn2) and Centruroides suffusus suffusus (Css2). Here we present the crystal structure of the complex formed between one scFv (9004G) and the Cn2 toxin, determined in two crystal forms at 2.5 and 1.9 Å resolution. A 15-residue span of the toxin is recognized by the antibody through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…3A). The structure of the Cn2 toxin in the ternary complex is virtually the same as that in the 9004G-Cn2 crystallographic structure (14), with a root mean square deviation between both Cn2 toxin structures of only 0.507 Å. This is also similar to the NMR solution structure already reported for this toxin (38).…”
Section: Crystallization Of the Ternary Complex-supporting
confidence: 71%
See 3 more Smart Citations
“…3A). The structure of the Cn2 toxin in the ternary complex is virtually the same as that in the 9004G-Cn2 crystallographic structure (14), with a root mean square deviation between both Cn2 toxin structures of only 0.507 Å. This is also similar to the NMR solution structure already reported for this toxin (38).…”
Section: Crystallization Of the Ternary Complex-supporting
confidence: 71%
“…2), which explained the complementary neutralization activity of the two scFvs (RU1 and LR), prompting us to identify the second interaction site on the Cn2 toxin. The first binding site on the Cn2 toxin, which was recognized by scFv LR and was confirmed in this work, allowed us to reinforce the available information related to the toxin areas that interact with the sodium channel and the proposed neutralization mechanisms (14,40). The new binding site on the Cn2 toxin, which was structurally opposite the one recognized by scFv LR, is composed of the N-terminal segment, including residues Leu 5 , Val .…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The interactions in the V H -V L interface area were analyzed in all the models and compared with the structure of the scFv 9004G, an antibody that neutralizes the Cn2 toxin, which present high homology with the scFv 6009F [43]. In this interface zone, all the structures from the scFv 9004G showed that two residues of the CDR L3 (Q221 and R228) as well as one of the framework-2 (Y168) interact, by hydrogen bonds, with two residues of the CDR H3 (G102 and F104), when the Cn2 toxin is present (Fig.…”
Section: Structural Analysis Of Different Formats Of 6009fmentioning
confidence: 99%